2018
DOI: 10.1016/j.heliyon.2018.e01020
|View full text |Cite
|
Sign up to set email alerts
|

Environmental assessment of ozone layer depletion due to the manufacture of plastic bags

Abstract: The results of a quantitative study about the potential environmental impact of ozone layer depletion due to the manufacture of plastic bags in a plant located in northern Colombia are presented in this article. The identification of the emitted gases is essential to determine their contribution to the depletion of the ozone layer and is measured in Kg. Eq. CFC-11 with LCA software, SimaPro. The criterion used in this evaluation are based on a life cycle analysis methodology and the objectives, scope and limit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 18 publications
1
11
0
Order By: Relevance
“…Unlike the HDPE bottle, the PET bottle showed up as a maximum indicator in some CML impact categories. The categories in which PET was maximum indicator in the pressurised and fruit juice categories ('Depletion of Abiotic Resources -elements, ultimate reserves' and 'Ozone Layer Depletion') are in line with other studies (Accorsi et al, 2015;Morales-Méndez and Silva-Rodríguez, 2018). The biggest factor in both of these impacts is the production of plastic granules, which encompasses inputs and outputs of mining raw materials, processing, and preparation for manufacture.…”
Section: Key Resultssupporting
confidence: 86%
“…Unlike the HDPE bottle, the PET bottle showed up as a maximum indicator in some CML impact categories. The categories in which PET was maximum indicator in the pressurised and fruit juice categories ('Depletion of Abiotic Resources -elements, ultimate reserves' and 'Ozone Layer Depletion') are in line with other studies (Accorsi et al, 2015;Morales-Méndez and Silva-Rodríguez, 2018). The biggest factor in both of these impacts is the production of plastic granules, which encompasses inputs and outputs of mining raw materials, processing, and preparation for manufacture.…”
Section: Key Resultssupporting
confidence: 86%
“…Specifically, the fossil fuels and oil‐derived materials used for LDPE production were the largest contributors to global warming, smog and respiratory effects. Global warming is known as a primary cause of ozone layer depletion 30 …”
Section: Resultsmentioning
confidence: 99%
“…A recent study assessed the contribution of the various stages of the plastic bag production process to atmospheric pollution by quantifying the ozone layer depletion category. The results showed that the process contributing the most pollution was the extrusion process of plastic bags, followed by the printing process, which accounts for about 50% and 30% of the total contribution, respectively [9]. The extrusion process of plastic film has the most significant degree of ozone layer depletion.…”
Section: Current Pollution Caused By Plastic Bagsmentioning
confidence: 99%
“…This is where raw materials such as natural gas and oil enter the plastic bag manufacturing process. The printing section of plastic bags is the second process that has a significant environmental impact on the ozone layer because this process uses a large number of chemicals, such as alcohol, acetic acid, and ink [9].…”
Section: Current Pollution Caused By Plastic Bagsmentioning
confidence: 99%